2017
DOI: 10.1016/j.jsams.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Wearable microtechnology can accurately identify collision events during professional rugby league match-play

Abstract: Objectives: Collision frequency during rugby league matches is associated with team success, greater and longer lasting fatigue and increased injury risk. This study researched the sensitivity and specificity of microtechnology to count collision events during rugby league matches. Design: Diagnostic accuracy studyMethods: While wearing a microtechnology device (Catapult, Optimeye S5), eight professional rugby league players were subjected to a total of 380 collision events during matches. Video footage of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 31 publications
1
90
2
Order By: Relevance
“…Convolutional neural networks have previously been applied to a single wearable sensor's accelerometer output to identify 10 different specific strikes in beach volleyball at a single level of classification with a lower classification accuracy of 83.2% [33]. The results of the current study are closer to those of machine learning programmes which have been developed for the recognition of bowling tasks in cricket (99% specificity and 98.1% sensitivity) [25] and tackles in rugby (97.6% accuracy) [27]. While manufacturer-developed algorithms have been developed to detect jumping on other sporting populations with similar accuracy, these have not been validated in dancespecific jumps [14,15].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Convolutional neural networks have previously been applied to a single wearable sensor's accelerometer output to identify 10 different specific strikes in beach volleyball at a single level of classification with a lower classification accuracy of 83.2% [33]. The results of the current study are closer to those of machine learning programmes which have been developed for the recognition of bowling tasks in cricket (99% specificity and 98.1% sensitivity) [25] and tackles in rugby (97.6% accuracy) [27]. While manufacturer-developed algorithms have been developed to detect jumping on other sporting populations with similar accuracy, these have not been validated in dancespecific jumps [14,15].…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, the aesthetics of ballet focus on clean, unimpeded movements and line of the leg and torso, in both training and performance settings [36]. It is unlikely that an elite dancer or athlete would regularly wear six sensors and within other sports a single upper back worn sensor is more common [25,27]. Our study demonstrated a single sensor worn on the upper back having the poorest accuracy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The teacher and tactical [31,32,35], as well as neuromuscular (player load, impacts, etc.) [36,37] effort required to play football. Similarly, to quantify eTL subjectively, one can use the Integral System for the Analysis of Training Tasks (SIATE in its Spanish acronym); this system studies the pedagogical and organizational variables that define a task, and also makes it possible for teachers to quantify the subjective eTL of the tasks used to teach contact sports (eTL task = sum of the assigned value, from 1 to 5 points, of each of the six categories of ordinal load variables: degree of opposition, density of the task, percentage of simultaneous performers, competitive load, game space, and cognitive implication) [38].…”
Section: Introductionmentioning
confidence: 99%
“…Smart sensors are fast becoming key tools in performance analysis for decreasing the time of direct observation with optimal validity [13,16]. The symbiosis between both instruments (performance analysis and smart devices), has focused its development in high-performance sport, mainly [11] because of the desire for performance improvement and control of the training load in many sports, e.g., soccer [17,18], football [19], basketball [20], rugby [21,22], and tennis [3,13,23]. Meanwhile, the study in recreational and educational contexts is still at an early stage of development, meaning that the present and future usefulness of both tools cannot be known [24,25].…”
Section: Introductionmentioning
confidence: 99%